2012
DOI: 10.1111/exd.12065
|View full text |Cite
|
Sign up to set email alerts
|

Galectin‐7 and actin are components of amyloid deposit of localized cutaneous amyloidosis

Abstract: The precursor protein of localized cutaneous amyloidosis (LCA) is believed to be cytokeratins on the basis of previous immunohistochemical studies. To identify the candidate amyloid protein biochemically, amyloid proteins were extracted with distilled water from lesional skin of LCA associated with Bowen's disease. The proteins were resolved on one- or two-dimensional polyacrylamide gel electrophoresis followed by characterization with immunoblot analysis. The proteins with multiple molecular weights of 50-67 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
1
19
0
2
Order By: Relevance
“…Cytokeratin 5 is predominantly found in basal keratinocytes (25,26). In the pathogenesis of amyloidosis, a commonly accepted theory is that the apoptotic basal keratinocytes (colloid bodies) release cytokeratins, which are then covered with autoantibodies, phagocytized by macrophages, and enzymatically degraded to amyloid K (keratin-associated amyloid).…”
Section: Discussionmentioning
confidence: 99%
“…Cytokeratin 5 is predominantly found in basal keratinocytes (25,26). In the pathogenesis of amyloidosis, a commonly accepted theory is that the apoptotic basal keratinocytes (colloid bodies) release cytokeratins, which are then covered with autoantibodies, phagocytized by macrophages, and enzymatically degraded to amyloid K (keratin-associated amyloid).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the secondary structure of cytokeratin consisits of ␣-helical, coiled-coil rod domains (5), whereas more than 20 amyloidogenic proteins that can bind Congo red or ThT share common cross-␤ sheet structures, which is defined as ␤-fibrillosis (6). Recently, we identified galectin-7 (Gal-7), actin, and cytokeratins as well as serum amyloid P component (SAP) and apolipoprotein E (Apo E) as the major components of amyloid deposits of PLCA in the water soluble fraction recovered from lesional skin, and we found that all of these proteins were present in the amyloid deposits of PLCA according to immunohistochemical studies (2,(7)(8)(9). SAP and Apo E are universal nonfibrillar constituents of amyloid deposits and will therefore be excluded from the candidates for amyloid precursor protein.…”
Section: Primary Localized Cutaneous Amyloidosis (Plca)mentioning
confidence: 90%
“…Amyloid fibrils were sequentially extracted from the lesional skin of localized cutaneous amyloidosis with distilled water as described previously (7). The yield of the protein in the watersoluble fraction was ϳ90 g.…”
Section: Methodsmentioning
confidence: 99%
“…PLOA etiopatogenezė nėra žinoma, liga gali būti idiopatinė arba susijusi su genetine predispozicija [2,7]. Ši amiloidozės forma dažnai siejama su epidermio pažeidimu dėl lėtinės trinties (prurigo nodularis, lichen simplex chronicus, lėtinis niežėjimas) [2,4,8], Epštein-Baro viruso (EBV) infekcija [2], ultravioletiniais B spinduliais, rasine priklausomybe, atopija [5,7,9] ir trauma [10]. mo laikotarpiu, ja nežymiai dažniau serga moterys [4,5].…”
unclassified
“…Dažniausi jų: bazoląstelinė ir plokščialąstelinė karcinoma, seborėjinė bei aktininė keratozė, intradermalinis melanocitinis ir linijinis karpinis epiderminis apgamas, prakaito liaukų navikai, pilomatriksoma, dermatofibroma, fotojautri žiedinė elastinė gigantinių ląstelių granulioma, Mibelli'o porokeratozė, trichoepitelioma, trichoblastoma, Bowen'o ligos ir odos T-ląstelių limfomos (mycosis fungoides) išraiškos odoje [1,2,4,8]. Panašus fenomenas gali būti stebimas po PUVA terapijos [1,4].…”
unclassified